Promoting Indonesian Cultural Practices through August 17th Games: A Community Service Program in Thailand - Zahratus Syifa; Abdul Rohim; Aidil Syah Putra (JURNAL ABDIMAS MADUMA, 2026)
Students in international schools may have limited opportunities to get to know Indonesian culture firsthand. This community service program aims to introduce social values with education in the celebration of August 17 through simple games at Islamwittaya Foundation School, Thailand. The method used is a participatory method that is carried out using four stages, including planning, implementation, observation, and mentoring. The data collected was by direct observation with photo documentation, then analyzed descriptively based on participation, compliance with rules, cooperation, and sportsmanship. Cultural introduction was analyzed as an additional outcome of the program. Activities are adjusted to the conditions in the classroom, student characteristics, facilities, and school schedule. The results of observations indicate that students have a high level of participation, compliance, cooperation, and sportsmanship in individual, pair, or group activities. They communicate, divide roles, help friends, follow the rules, by accepting the outcome of the game without dispute. Photo documentation also indicates that the activity took place in an orderly and enjoyable manner. Because it does not use a pre-test or post-test, the standard attitude scale, the results of the study only indicate a direct response of students, not long-term changes in cultural understanding. The program indicates that simple, low-cost games can provide cross-cultural experiences, strengthen social interactions, and support experiential learning. This activity model can also be implemented by schools or service teams without disrupting routine learning. Keywords : August 17th Games; Indonesian Cultural Practices; Experiential Learning; Cross-Cultural Awareness